A solid oxide fuel cell and its preparation method and application
通过在固体氧化物燃料电池中采用多层致密的复合电解质层和复合阴极层的结构,结合高活性抗积碳的钙钛矿结构材料和铜修饰的掺杂氧化材料,解决了低温下甲醇燃料 Battery performance and stability problems have achieved high performance and low -cost battery preparation.
Patent Information
- Application Number
- CN202411295445.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-18
AI Technical Summary
When solid oxide fuel cells use methanol fuel at low temperatures, their performance is low. Complex electrochemical processes and carbon coking lead to loss of anode activity, poor stability, and difficult to meet commercial requirements.
Adopt a multi -layer dense composite electrolyte layer and the structure of the composite cathode layer. The anode supporting body includes high -active carbon ingot ingot structure materials, nickel catalytic materials, and doped oxidation cymbal materials. The doped oxidation cymbal material and oxide base materials are prepared by wet chemical legal.
At low temperature, the battery has a high voltage, excellent performance, good stability, and low cost in the preparation process. It is easy to place and has high reliability.
Smart Images

Figure CN118825347B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cells, and in particular to a solid oxide fuel cell and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Energy and environment have become two hot issues related to the sustainable development of human society. With the continuous advancement of the modernization process of human society, the contradiction between dependence on energy and the depletion of fossil energy is becoming increasingly severe. A large amount of pollutants and greenhouse gases such as CO2 are emitted during the production and use of energy, which is one of the important sources of air pollution. Finding clean, efficient and low-net-CO2 energy technologies has become an urgent need for the development of human society.
[0004] As an energy conversion device, solid oxide fuel cells can efficiently convert chemical energy in fuels (such as methanol, natural gas, ethanol, etc.) into electrical energy. They have the characteristics of high power generation efficiency, wide fuel application range, and low emissions. The reduction of the operating temperature of solid oxide fuel cells can greatly speed up their start and stop speed, and expand the scope of application from traditional fixed applications to portable applications. Methanol, as a clean fuel, has a wide range of sources. It can be obtained from agricultural and animal by-products. It can also be used to produce hydrogen by electrolyzing water using renewable energy such as solar energy and wind energy. The reaction of hydrogen and CO2 can achieve clean preparation of methanol.
[0005] Methanol is a renewable energy source with the characteristics of high volumetric energy density, cleanliness and portability. Therefore, the use of methanol as a fuel for solid oxide fuel cells has begun to arouse great research interest. However, when using methanol as fuel, the performance of solid oxide fuel cells is relatively low compared with hydrogen-based fuel cells. The complex electrochemical process and carbon coking will significantly increase the activity loss of the anode. Especially when working at low temperatures, the battery performance is low and carbon deposition is easy to occur, resulting in poor battery stability. Therefore, low-temperature high performance and high stability are crucial for methanol-fueled solid oxide fuel cells to meet the requirements of commercialization. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a low-temperature, high-performance, high-stability solid oxide fuel cell and a preparation method thereof. The low-temperature, high-performance, high-stability solid oxide fuel cell of the present invention comprises an anode support, a multi-layer dense composite electrolyte layer arranged on the anode support, and a cathode layer arranged on the composite electrolyte layer. Among them, the anode support comprises a perovskite structural material, a nickel catalytic material, and a doped cerium oxide-based material; the composite electrolyte layer comprises a doped cerium oxide electrolyte layer, a copper-modified doped zirconium oxide electrolyte layer, and a copper-modified doped cerium oxide electrolyte layer. When the solid oxide fuel cell prepared by the present invention uses methanol fuel, it has the characteristics of high open circuit voltage, high performance, good stability, etc. at low temperature, and the battery preparation process adopts a low-cost wet chemical method, and the prepared solid oxide fuel cell has the characteristics of low cost, easy amplification, good reliability, etc.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] In a first aspect, the present invention provides a solid oxide fuel cell, comprising:
[0009] an anode support;
[0010] A multi-layer composite electrolyte layer disposed on the anode support;
[0011] a composite cathode layer disposed on the composite electrolyte layer;
[0012] The anode support comprises an anode catalyst and a doped cerium oxide-based material;
[0013] The anode catalyst comprises a perovskite structure material and a nickel catalytic material;
[0014] The composite electrolyte layer includes a doped cerium oxide electrolyte layer, a copper-modified doped zirconia electrolyte layer, and a copper-modified doped cerium oxide electrolyte layer.
[0015] In one or more embodiments, in the anode support, the mass percentages of the high-activity anti-carbon deposition perovskite structural material, the high-conductivity nickel catalytic material and the doped cerium oxide-based material are (1-40):(20-60):(20-60), and the total mass of the three is 100.
[0016] In one or more embodiments, the thickness of the anode support is 200 to 2000 microns.
[0017] In one or more embodiments, the structural formula of the highly active anti-carbon deposition perovskite structural material is: [La (1-x-y) Sr x Mg y ] z Ti(1-a-b-c) Cu a Zn b Ni c O 3±δ , δ represents the non-stoichiometric value of oxygen produced by doping, 0.1≤x≤0.8, 0.01≤y≤0.4, 0.8≤z≤1.1, 0.01≤a≤0.2, 0.01≤b≤0.2, 0.01≤c≤0.2.
[0018] In one or more embodiments, the nickel catalytic material is nickel oxide.
[0019] In one or more embodiments, the doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5.
[0020] In one or more embodiments, the thickness of the doped cerium oxide-based electrolyte layer is 1 to 50 micrometers.
[0021] In one or more embodiments, the copper-modified doped zirconia-based electrolyte layer has a thickness of 0.01 to 5 microns.
[0022] In one or more embodiments, the copper-modified doped cerium oxide-based electrolyte layer has a thickness of 1 to 10 micrometers.
[0023] In one or more embodiments, in the doped cerium oxide electrolyte layer, the doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5.
[0024] In one or more embodiments, in the copper-modified doped zirconia electrolyte layer, the copper-modified doped zirconia-based material is Cu j M n Zr 1-n O2, 0.01≤j≤0.2, M is one or more of Y, Sc, Ce, 0.01≤n≤0.5.
[0025] In one or more embodiments, in the copper-modified doped cerium oxide electrolyte layer, the copper-modified doped cerium oxide-based material is Cu k Ln m Ce 1-m O2, 0.01≤k≤0.2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5.
[0026] In one or more embodiments, the composite cathode layer is a cobalt-based composite cathode layer, including lanthanum strontium cobalt iron powder (La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3, LSCF) and doped ceria-based materials.
[0027] The thickness of the composite cathode layer is 10-100 microns, preferably 20-60 microns.
[0028] The doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5, preferably doped cerium oxide (Gd 0.2 Ce 0.8 O2, GDC).
[0029] The weight ratio of the lanthanum strontium cobalt iron powder to the doped cerium oxide-based material is (30-100): (0-70).
[0030] In a second aspect, the present invention provides a method for preparing the above-mentioned solid oxide fuel cell, comprising the following steps:
[0031] (1) Composite a perovskite structural material, a nickel catalytic material and a doped cerium oxide-based material to form an anode support;
[0032] (2) preparing a multi-layer dense composite electrolyte layer on the anode support by a wet chemical method;
[0033] (3) Preparing a composite cathode layer on the multi-layer dense composite electrolyte layer, and subjecting it to high-temperature calcination treatment, to obtain a low-temperature, high-performance, and high-stability solid oxide fuel cell.
[0034] In one or more embodiments, in step (1), the composite process of the anode support includes a tape casting method, an extrusion molding method, etc. The tape casting method is preferred.
[0035] In one or more embodiments, in step (1), the anode catalyst is prepared by compounding the perovskite structure material with the nickel catalytic material, and then the electrode catalyst is compounded with the doped cerium oxide-based material to prepare the anode support.
[0036] In one or more embodiments, in step (2), the specific steps of preparing a multi-layer dense composite electrolyte layer on the anode support by wet chemical method include:
[0037] Step a: preparing a doped cerium oxide-based electrolyte film on one side of the anode support by a coating method, and performing high-temperature calcination treatment to obtain a dense doped cerium oxide electrolyte layer;
[0038] Step b: on the dense doped cerium oxide electrolyte layer, a copper-modified doped zirconia electrolyte layer is prepared by a coating method, and high-temperature calcination is performed to obtain a dense copper-modified doped zirconia electrolyte layer;
[0039] Step c: on the dense copper-modified doped zirconium oxide electrolyte layer, a copper-modified doped cerium oxide electrolyte layer is prepared by a coating method, and high-temperature calcination is performed to obtain a dense copper-modified doped cerium oxide electrolyte layer.
[0040] In one or more embodiments, in step a, the coating method includes screen printing or film coating; the high temperature calcination treatment is performed at 1200 to 1500 o C is roasted for 2 to 20 hours.
[0041] In one or more embodiments, in step b, the coating method includes spraying or film coating; the high temperature calcination treatment is performed at 1000 to 1300 o C is roasted for 2 to 20 hours.
[0042] In one or more embodiments, in step b, the calcination temperature is 1100-1200 o C.
[0043] In one or more embodiments, in step c, the coating method includes spraying or film coating; the high temperature calcination treatment is performed at 1000 to 1300 o C is roasted for 2 to 20 hours.
[0044] In one or more embodiments, in step c, the calcination temperature is 1100-1200 o C.
[0045] In one or more embodiments, in step (3), a composite cathode layer is prepared on the copper-modified doped cerium oxide electrolyte layer by a coating method, and the high temperature calcination treatment is 800-1200 o C.
[0046] In one or more embodiments, in step (3), the coating method includes screen printing or film coating.
[0047] In a third aspect, the present invention provides an application of the above-mentioned low-temperature, high-performance and high-stability solid oxide fuel cell in energy conversion.
[0048] In one or more embodiments, the energy is converted to methanol as a fuel.
[0049] In one or more embodiments, the energy is converted to methanol as fuel at low temperature, wherein the low temperature is 500-650°C.
[0050] One or some of the above technical solutions have the following advantages or beneficial effects:
[0051] 1. The low-temperature, high-performance, high-stability solid oxide fuel cell prepared by the present invention is composed of an anode support, a multi-layer dense composite electrolyte layer arranged on the anode support, and a cathode layer arranged on the composite electrolyte layer. The anode support includes an anode catalyst and a doped cerium oxide-based material. The anode catalyst is composed of a highly active carbon-deposition-resistant perovskite structure material and a nickel catalyst material skeleton. The perovskite structure highly active catalyst material [La (1-x-y) Sr x Mg y ] z Ti (1-a-b-c) Cu a Zn b Ni c O 3±δ , which can efficiently convert methanol and effectively improve the battery's anti-carbon deposition performance, so that when it uses methanol as fuel, it has the characteristics of high open circuit voltage, high low-temperature battery performance, and good stability.
[0052] 2. The present invention adopts a coating method to prepare a composite electrolyte layer, wherein a copper-modified doped zirconium oxide-based material and a copper-modified doped cerium oxide-based material are used in the second and third layers. The addition of copper plays a role in sintering, reduces the sintering temperature, reduces the cost, and avoids the high-temperature reaction of the cerium oxide-based material and the zirconium oxide-based material to form a high-impedance cerium-zirconium oxide solid solution.
[0053] 3. The battery preparation process of the present invention adopts low-cost wet chemical methods. The prepared solid oxide fuel cells have the characteristics of low cost, easy scale-up, good reliability, etc., which is of great significance for promoting the practical application of solid oxide fuel cell technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0055] Figure 1 The SEM images of the anode supports prepared in Example 2 and Example 3; wherein (a), (b), (c) are SEM images of the anode supports prepared in Example 2, and (a), (b), (c) refer to the SEM images of the anode supports magnified by 20,000 times, 100,000 times, and 150,000 times, respectively; (d), (e), (f) are SEM images of the anode supports prepared in Example 3, and (d), (e), (f) refer to the SEM images of the anode supports magnified by 20,000 times, 100,000 times, and 150,000 times, respectively;
[0056] Figure 2 The power density curves of the traditional Ni-GDC / GDC / LSCF-GDC battery and the high-performance battery prepared in Example 3 at different temperatures; wherein (a) is the power density curve of the traditional Ni-GDC / GDC / LSCF-GDC battery, and (b) is the power density curve of the high-performance battery prepared in Example 3; the different temperatures include 500°C, 550°C, 600°C and 650°C;
[0057] Figure 3 The stability test results of the traditional Ni-GDC / GDC / LSCF-GDC battery and the high-performance battery prepared in Example 3 using methanol as fuel under constant current conditions; wherein, (a) is the stability test result of the traditional Ni-GDC / GDC / LSCF-GDC battery under constant current conditions, and (b) is the stability test result of the high-performance battery prepared in Example 3 using methanol as fuel under constant current conditions. DETAILED DESCRIPTION
[0058] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0059] The core innovation of the present invention is that the anode catalyst material used and the second and third layers of the composite electrolyte layer innovatively adopt copper-modified doped zirconium oxide-based materials (Cu j M n Zr 1-n O2) and copper-modified doped ceria-based materials (Cu k Ln m Ce 1-m O2), these are the two major innovations of the present invention.
[0060] When methanol fuel is used, compared with hydrogen fuel cell, the performance of solid oxide fuel cell is relatively low, and the complex electrochemical process and carbon coking will significantly increase the activity loss of the anode, especially when working at low temperature, the battery performance is low and carbon deposition is easy to occur, resulting in poor battery stability. Therefore, in the present invention, the solid oxide fuel cell uses copper-modified doped zirconium oxide-based materials as the electrolyte electron blocking layer, which can effectively block the electronic conductivity of the doped cerium oxide-based electrolyte, so that the battery has higher performance and open circuit voltage at low temperature, and then the anode catalyst is formed by the highly active anti-carbon deposition perovskite structural material and the nickel catalytic material skeleton, and the anode support is obtained by combining with the doped cerium oxide-based material, wherein the perovskite structural material has the effect of high activity anti-carbon deposition, so that the solid oxide fuel cell finally prepared can solve the problem of anti-carbon deposition at low temperature when methanol is used as fuel, so that the battery has high stability and has the characteristics of low temperature, high performance and high stability.
[0061] The composite electrolyte layer includes a doped cerium oxide electrolyte layer, a copper-modified doped zirconium oxide electrolyte layer, and a copper-modified doped cerium oxide electrolyte layer. Among them, when preparing a dense electrolyte layer, if the magnetron sputtering method is used, the process cost is often increased, but if the low-cost coating method is used, a higher sintering temperature is required, generally it may be above 1400°C to prepare a dense zirconium oxide or cerium oxide electrolyte layer, but at the same time, due to the high sintering temperature, the doped cerium oxide and the doped zirconium oxide may react at this time, resulting in the battery having no performance. Therefore, when preparing the composite electrolyte layer, the present application innovatively uses copper-modified doped zirconium oxide-based materials and copper-modified doped cerium oxide-based materials in the second and third layers, and introduces copper to play a role in sintering, thereby reducing the sintering temperature when preparing a dense electrolyte layer by the coating method, generally between 1000 and 1300°C. o C, preferably 1100-1200 o C, the dense electrolyte layer can be prepared. At this time, due to the reduction of sintering temperature, the doped cerium oxide and the doped zirconia will not react. Therefore, the addition of copper not only reduces the process cost, can use a simple coating method, but also reduces the sintering temperature, avoids the high-impedance cerium-zirconium oxide solid solution generated by the high-temperature reaction between the cerium oxide-based electrolyte separator and the zirconia-based electrolyte layer during the preparation process, and effectively prevents the chemical reaction and element diffusion between the high-activity cobalt composite cathode layer and the copper-doped zirconia-based electrolyte layer.
[0062] In a typical embodiment, the present invention provides a low-temperature, high-performance, high-stability solid oxide fuel cell, comprising:
[0063] an anode support;
[0064] A multi-layer dense composite electrolyte layer is disposed on the anode support;
[0065] a composite cathode layer disposed on the composite electrolyte layer;
[0066] The anode support includes an anode catalyst and a doped ceria-based material.
[0067] In some examples of this embodiment, the anode catalyst is composed of a highly active and carbon deposition resistant perovskite structural material and a nickel catalytic material, so that the prepared anode catalyst has the characteristics of high activity and carbon deposition resistance.
[0068] In some examples of this embodiment, in the anode support, the mass ratio of the perovskite structural material, the nickel catalytic material and the doped cerium oxide-based material is (1-40):(20-60):(20-60).
[0069] In some examples of this embodiment, the thickness of the anode support is 200-2000 microns, preferably 400-1200 microns.
[0070] In some examples of this embodiment, the structural formula of the highly active anti-carbon deposition perovskite structural material is: [La (1-x-y) Sr x Mg y ] z Ti (1-a-b-c) Cu a Zn b Ni c O 3±δ , δ represents the oxygen non-stoichiometric value generated by doping, 0.1≤x≤0.8, 0.01≤y≤0.4, 0.8≤z≤1.1, 0.01≤a≤0.2, 0.01≤b≤0.2, 0.01≤c≤0.2. The preparation process of the perovskite structure material is not particularly limited. In the present invention, the preparation process of the perovskite structure material is a sol-gel method or a glycine method.
[0071] The nickel catalytic material is nickel oxide. When the nickel oxide is subsequently sintered and reduced, nickel is formed, and nickel has the advantage of high electrical conductivity.
[0072] The doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5.
[0073] In some examples of this embodiment, the composite electrolyte layer includes a doped cerium oxide electrolyte layer, a copper-modified doped zirconium oxide electrolyte layer, and a copper-modified doped cerium oxide electrolyte layer, wherein copper plays a role in sintering.
[0074] In some examples of this embodiment, the thickness of the doped cerium oxide-based electrolyte layer is 1 to 50 micrometers, preferably 2 to 40 micrometers, and more preferably 10 to 40 micrometers.
[0075] In some examples of this embodiment, the thickness of the copper-modified doped zirconia-based electrolyte layer is 0.01 to 5 micrometers, preferably 0.02 to 3 micrometers, and more preferably 0.2 to 2 micrometers.
[0076] In some examples of this embodiment, the thickness of the copper-modified doped cerium oxide-based electrolyte layer is 1 to 10 microns, preferably 2 to 6 microns.
[0077] In some examples of this embodiment, in the doped cerium oxide electrolyte layer, the doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5.
[0078] In some examples of this embodiment, in the copper-modified doped zirconia electrolyte layer, the copper-modified doped zirconia-based material is Cu j M n Zr 1-n O2, 0.01≤j≤0.2, M is one or more of Y, Sc, Ce, 0.01≤n≤0.5.
[0079] In some examples of this embodiment, in the copper-modified doped cerium oxide electrolyte layer, the copper-modified doped cerium oxide-based material is Cu k Ln m Ce 1-m O2, 0.01≤k≤0.2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5.
[0080] In some examples of this implementation manner, the composite cathode layer is a cobalt-based composite cathode layer, including lanthanum strontium cobalt iron powder and doped cerium oxide-based material.
[0081] The thickness of the composite cathode layer is 10-100 microns, preferably 20-60 microns.
[0082] The doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5, preferably doped cerium oxide (Gd 0.2 Ce 0.8 O2, GDC).
[0083] The weight ratio of the lanthanum strontium cobalt iron powder to the doped cerium oxide-based material is (30-100): (0-70).
[0084] In another embodiment, the present invention provides a method for preparing the above-mentioned low-temperature, high-performance and high-stability solid oxide fuel cell, comprising the following steps:
[0085] (1) Composite a perovskite structural material, a nickel catalytic material and a doped cerium oxide-based material to form an anode support;
[0086] (2) preparing a multi-layer dense composite electrolyte layer on the anode support by a wet chemical method;
[0087] (3) Preparing a composite cathode layer on the multi-layer dense composite electrolyte layer, and subjecting it to high-temperature calcination treatment, to obtain a low-temperature, high-performance, and high-stability solid oxide fuel cell.
[0088] In some examples of this implementation mode, in the step (1), a high-activity anode catalyst is prepared by compounding a perovskite structure material with a nickel catalytic material, and then the high-activity anode catalyst is compounded with a doped cerium oxide-based material to prepare an anode support.
[0089] In the step (1), the composite process of the anode support includes a casting method, an extrusion molding method, etc. The composite process used in the embodiment of the present invention is a casting method, wherein the casting method is well known to those skilled in the art.
[0090] In some examples of this implementation mode, in step (2), the specific steps of preparing a multi-layer dense composite electrolyte layer on the anode support by wet chemical method include:
[0091] Step a: preparing a doped cerium oxide-based electrolyte film on one side of the anode support by a coating method, and performing high-temperature calcination treatment to obtain a dense doped cerium oxide electrolyte layer;
[0092] Step b: on the dense doped cerium oxide electrolyte layer, a copper-modified doped zirconia electrolyte layer is prepared by a coating method, and high-temperature calcination is performed to obtain a dense copper-modified doped zirconia electrolyte layer;
[0093] Step c: on the dense copper-modified doped zirconium oxide electrolyte layer, a copper-modified doped cerium oxide electrolyte layer is prepared by a coating method, and high-temperature calcination is performed to obtain a dense copper-modified doped cerium oxide electrolyte layer.
[0094] In some embodiments of this embodiment, in step a, the coating method includes screen printing or film coating; the high temperature calcination treatment is performed at 1200 to 1500 o C is roasted for 2 to 20 hours.
[0095] In some embodiments of this embodiment, in step b, the coating method includes spraying or film coating; the high temperature calcination treatment is performed at 1000 to 1300 o C is roasted for 2 to 20 hours.
[0096] In some examples of this embodiment, in step c, the coating method includes spraying or film coating; the high temperature calcination treatment is performed at 1000 to 1300 o C is roasted for 2 to 20 hours.
[0097] In some examples of this embodiment, in step (3), a composite cathode layer is prepared on the copper-modified doped cerium oxide electrolyte layer by a coating method, and the high temperature calcination treatment is 800-1200 o C.
[0098] In step (3), the coating method includes screen printing or film coating.
[0099] As a preferred method, a preparation method of a low-temperature, high-performance, high-stability solid oxide fuel cell comprises the following steps: preparing a high-activity electrode catalyst by compounding a high-activity carbon deposition-resistant perovskite structural material with a nickel catalytic material, and then compounding the high-activity electrode catalyst with a doped cerium oxide-based electrolyte material to prepare an anode support; preparing a doped cerium oxide-based electrolyte film on one side of the anode support by screen printing or coating, and o C is calcined for 2 to 20 hours to obtain a dense cerium oxide-based electrolyte layer; on the dense cerium oxide-based electrolyte layer, a copper-modified doped zirconium oxide electrolyte layer is prepared by a spraying method or a coating method, and the temperature is 1000 to 1300 o C for 2 to 20 hours to obtain a dense copper-modified doped zirconium oxide electrolyte layer; on the dense copper-modified doped zirconium oxide electrolyte layer, a copper-modified doped cerium oxide electrolyte layer is prepared by a spraying method or a coating method, and the copper-modified doped cerium oxide electrolyte layer is prepared by a spraying method or a coating method at 1000 to 1300 o C is calcined for 2 to 20 hours to obtain a dense copper-modified doped cerium oxide electrolyte layer; a cobalt-based composite cathode layer is prepared on the copper-modified doped cerium oxide electrolyte layer by screen printing or coating to obtain a low-temperature, high-performance, and high-stability solid oxide fuel cell.
[0100] The present invention also provides an application of the above-mentioned low-temperature, high-performance and high-stability solid oxide fuel cell in the process of using methanol as fuel.
[0101] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0102] Example 1
[0103] The high activity and carbon deposition resistant perovskite structure material [La 0.3 Sr 0.5 Mg 0.2 ] 1.05 Ti 0.7 Cu 0.1 Zn 0.1 Ni 0.1 O 3±δ An anode support composed of a composite (mass ratio of 20:40:40) of nickel oxide and doped cerium oxide electrolyte material (Gd2O3 doped CeO2, GDC), with a thickness of about 800 microns;
[0104] On one side, Gd2O3-doped CeO2 (Gd 0.2 Ce 0.8 O2, GDC) electrolyte film, calcined at 1350℃ for 10 hours to obtain a dense doped cerium oxide-based electrolyte layer with a thickness of about 20 microns;
[0105] On the GDC electrolyte side, copper-modified yttria-stabilized zirconia (Y 0.08 Zr 0.92 O2, 8YSZ) thin layer electrolyte membrane, wherein the molar ratio of copper to 8YSZ is 0.04:1, and a dense copper-modified doped zirconia electrolyte layer with a thickness of about 0.5 microns is obtained by calcining at 1200°C for 8 hours;
[0106] On the copper-modified doped zirconia electrolyte layer, a copper-modified doped cerium oxide electrolyte layer was prepared by a coating method, wherein the molar ratio of copper to GDC was 0.04:1, and a dense copper-modified doped cerium oxide electrolyte layer with a thickness of about 2 μm was obtained by calcining at 1100° C. for 16 hours;
[0107] Then screen printing was used to prepare La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The composite cathode layer of O3 (LSCF) and GDC (60:40 by weight) is about 20 microns thick and is calcined at 1000°C for 2h to obtain a low-temperature, high-performance, and high-stability solid oxide fuel cell.
[0108] When this low-temperature, high-performance, high-stability solid oxide fuel cell uses methanol as fuel, the open circuit voltage of the cell is 1.05V when tested at 600°C, and the battery performance reaches 1200 mW / cm 2Compared with traditional Ni-GDC / GDC / LSCF-GDC batteries, the battery performance at 600°C is improved by about 90%; the battery is tested for stability at 600°C using methanol as fuel, and the attenuation rate per 100 hours is reduced by 60% compared with traditional Ni-GDC anode batteries.
[0109] Example 2
[0110] The high activity and carbon deposition resistant perovskite structure material [La 0.2 Sr 0.7 Mg 0.1 ] 0.9 Ti 0.8 Cu 0.05 Zn 0.05 Ni 0.1 O 3±δ The anode support is composed of a composite (mass ratio of 20:30:50) of nickel oxide and doped cerium oxide electrolyte material (Gd2O3 doped CeO2, GDC) (electron microscope photo as shown in Figure 1 As shown), thickness is about 1200 microns;
[0111] On one side, Gd2O3-doped CeO2 (Gd 0.2 Ce 0.8 O2, GDC) electrolyte film, calcined at 1400℃ for 4 hours to obtain a dense doped cerium oxide-based electrolyte layer with a thickness of about 40 microns;
[0112] On the GDC electrolyte side, copper-modified yttria-stabilized zirconia (Y 0.08 Zr 0.92 O2, 8YSZ) thin layer electrolyte membrane, wherein the molar ratio of copper to 8YSZ is 0.1:1, and a dense copper-modified doped zirconia electrolyte layer with a thickness of about 2 microns is obtained by calcining at 1100°C for 16 hours;
[0113] On the copper-modified doped zirconia electrolyte layer, a copper-modified doped cerium oxide electrolyte layer was prepared by a coating method, wherein the molar ratio of copper to GDC was 0.08:1, and a dense copper-modified doped cerium oxide electrolyte layer with a thickness of about 5 μm was obtained by calcining at 1100° C. for 12 hours;
[0114] Then screen printing is used to prepare La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The composite cathode layer of O3 (LSCF) and GDC (60:40 by weight) has a thickness of about 60 microns and is calcined at 1000°C for 2h to obtain a low-temperature, high-performance, and high-stability solid oxide fuel cell.
[0115] When this low-temperature, high-performance, high-stability solid oxide fuel cell uses methanol as fuel, the open circuit voltage of the cell is 1.06V when tested at 600°C, and the cell performance reaches 950 mW / cm 2 Compared with traditional Ni-GDC / GDC / LSCF-GDC batteries, the battery performance at 600°C is improved by about 50%; the battery stability test at 600°C using methanol as fuel shows that the attenuation rate per 100 hours is reduced by 80% compared with traditional Ni-GDC anode batteries.
[0116] Example 3
[0117] The high activity and carbon deposition resistant perovskite structure material [La 0.2 Sr 0.7 Mg 0.1 ] 0.9 Ti 0.8 Cu 0.075 Zn 0.075 Ni 0.05 O 3±δ The anode support is composed of a composite (mass ratio of 20:40:40) of nickel oxide and doped cerium oxide electrolyte material (Gd2O3 doped CeO2, GDC) (electron microscope photo as shown in Figure 1 As shown), thickness is about 1000 microns;
[0118] On one side, Gd2O3-doped CeO2 (Gd 0.2 Ce 0.8 O2, GDC) electrolyte film, calcined at 1300℃ for 12 hours to obtain a dense doped cerium oxide-based electrolyte layer with a thickness of about 10 microns;
[0119] On the GDC electrolyte side, copper-modified yttria-stabilized zirconia (Y 0.08 Zr 0.92 O2, 8YSZ) thin layer electrolyte membrane, wherein the molar ratio of copper to 8YSZ is 0.03:1, and a dense copper-modified doped zirconia electrolyte layer with a thickness of about 0.2 microns is obtained by calcining at 1200°C for 16 hours;
[0120] On the copper-modified doped zirconia electrolyte layer, a copper-modified doped cerium oxide electrolyte layer was prepared by a coating method, wherein the molar ratio of copper to GDC was 0.02:1, and a dense copper-modified doped cerium oxide electrolyte layer with a thickness of about 2 μm was obtained by calcining at 1200° C. for 12 hours;
[0121] Then screen printing is used to prepare La 0.6 Sr 0.4 Co 0.2 Fe 0.8The composite cathode layer of O3 (LSCF) and GDC (60:40 by weight) has a thickness of about 80 microns and is calcined at 900°C for 8 hours to obtain a low-temperature, high-performance, and high-stability solid oxide fuel cell.
[0122] When this low-temperature, high-performance, high-stability solid oxide fuel cell uses methanol as fuel, the open circuit voltage of the cell is 1.06V when tested at 600°C, and the cell performance reaches 1300 mW / cm 2 Compared with the traditional Ni-GDC / GDC / LSCF-GDC battery, the battery performance is improved by about 106% at 600℃ (e.g. Figure 2 As shown); The battery was tested for stability at 600℃ using methanol as fuel. Compared with the traditional Ni-GDC anode battery, the attenuation rate per 100 hours was reduced by 60% (as shown Figure 3 as shown).
[0123] Example 4
[0124] The high activity and carbon deposition resistant perovskite structure material [La 0.2 Sr 0.7 Mg 0.1 ] 0.8 Ti 0.8 Cu 0.05 Zn 0.05 Ni 0.1 O 3±δ An anode support composed of a composite (mass ratio of 10:50:40) of nickel oxide and doped cerium oxide electrolyte material (Gd2O3 doped CeO2, GDC), with a thickness of about 400 microns;
[0125] On one side, Gd2O3-doped CeO2 (Gd 0.2 Ce 0.8 O2, GDC) electrolyte film, calcined at 1450℃ for 4 hours to obtain a dense doped cerium oxide-based electrolyte layer with a thickness of about 20 microns;
[0126] On the GDC electrolyte side, copper-modified yttria-stabilized zirconia (Y 0.08 Zr 0.92 O2, 8YSZ) thin layer electrolyte membrane, wherein the molar ratio of copper to 8YSZ is 0.06:1, and a dense copper-modified doped zirconia electrolyte layer with a thickness of about 1 micron is obtained by calcining at 1200°C for 8 hours;
[0127] On the copper-modified doped zirconia electrolyte layer, a copper-modified doped cerium oxide electrolyte layer was prepared by a coating method, wherein the molar ratio of copper to GDC was 0.08:1, and a dense copper-modified doped cerium oxide electrolyte layer with a thickness of about 10 microns was obtained by calcining at 1200°C for 12 hours;
[0128] Then screen printing is used to prepare La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The composite cathode layer of O3 (LSCF) and GDC (60:40 by weight) is about 40 microns thick and is calcined at 1000°C for 2h to obtain a low-temperature, high-performance, and high-stability solid oxide fuel cell.
[0129] When this low-temperature, high-performance, high-stability solid oxide fuel cell uses methanol as fuel, the open circuit voltage of the cell is 1.06V when tested at 600°C, and the cell performance reaches 1150 mW / cm 2 Compared with traditional Ni-GDC / GDC / LSCF-GDC batteries, the battery performance at 600°C is improved by about 80%; the battery stability test at 600°C using methanol as fuel shows that the attenuation rate per 100 hours is reduced by 90% compared with traditional Ni-GDC anode batteries.
[0130] The present invention adopts a low-temperature, high-performance anode catalyst and a high-conductivity multilayer composite electrolyte to form a low-temperature, high-performance, high-stability solid oxide fuel cell. The perovskite structure catalytic material [La (1-x-y) Sr x Mg y ] z Ti (1-a-b-c) Cu a Zn b Ni c O 3±δ It can catalyze methanol conversion with high activity and direction, and can effectively improve the anti-carbon deposition performance of the battery. The low-temperature, high-performance and high-stability solid oxide fuel cell prepared by the present invention has the characteristics of high open circuit voltage, high low-temperature battery performance and good stability when using methanol as fuel. The solid oxide fuel cell of the present invention can greatly improve the low-temperature performance and stability of the battery.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A solid oxide fuel cell, characterized in that: include: an anode support; A multi-layer composite electrolyte layer disposed on the anode support; a composite cathode layer disposed on the composite electrolyte layer; The anode support comprises an anode catalyst and a doped cerium oxide-based material; The anode catalyst comprises a perovskite structure material and a nickel catalytic material; The composite electrolyte layer includes a doped cerium oxide electrolyte layer, a copper-modified doped zirconium oxide electrolyte layer, and a copper-modified doped cerium oxide electrolyte layer; The thickness of the anode support is 200 to 2000 microns; The structural formula of the perovskite structural material is: [La (1-x-y) Sr x Mg y ] z Ti (1-a-b-c) Cu a Zn b Ni c O 3±δ , δ represents the non-stoichiometric value of oxygen produced by doping, 0.1≤x≤0.8, 0.01≤y≤0.4, 0.8≤z≤1.1, 0.01≤a≤0.2, 0.01≤b≤0.2, 0.01≤c≤0.2; The solid oxide fuel cell uses methanol as fuel; The method for preparing the solid oxide fuel cell comprises the following steps: (1) Composite a perovskite structural material, a nickel catalytic material and a doped cerium oxide-based material to form an anode support; (2) preparing a multi-layer dense composite electrolyte layer on the anode support by a wet chemical method; (3) preparing a composite cathode layer on the multi-layer dense composite electrolyte layer, and performing high-temperature calcination treatment to obtain a solid oxide fuel cell; In step (2), a multi-layer dense composite electrolyte layer is prepared on the anode support by a wet chemical method, and the specific steps include: Step a: preparing a doped cerium oxide-based electrolyte film on one side of the anode support by a coating method, and performing high-temperature calcination treatment to obtain a dense doped cerium oxide electrolyte layer; Step b: on the dense doped cerium oxide electrolyte layer, a copper-modified doped zirconia electrolyte layer is prepared by a coating method, and high-temperature calcination is performed to obtain a dense copper-modified doped zirconia electrolyte layer; Step c: on the dense copper-modified doped zirconium oxide electrolyte layer, a copper-modified doped cerium oxide electrolyte layer is prepared by a coating method, and high-temperature calcination is performed to obtain a dense copper-modified doped cerium oxide electrolyte layer; In the step a, the coating method includes screen printing or film coating, and the high temperature calcination treatment is performed at 1200 to 1500 o C roasting for 2 to 20 hours; In the step b, the coating method includes a spraying method or a film coating method, and the high temperature calcination treatment is performed at 1100-1200 o C roasting for 2 to 20 hours; In the step c, the coating method includes a spraying method or a film coating method, and the high temperature calcination treatment is performed at 1100-1200 o C roasting for 2 to 20 hours; In the doped cerium oxide electrolyte layer, the doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5; In the copper-modified doped zirconia electrolyte layer, the copper-modified doped zirconia-based material is Cu j M n Zr 1- n O2, 0.01≤j≤0.2, M is one or more of Y, Sc, Ce, 0.01≤n≤0.5; In the copper-modified doped cerium oxide electrolyte layer, the copper-modified doped cerium oxide-based material is Cu k Ln m Ce 1- m O2, 0.01≤k≤0.2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.
5.
2. The solid oxide fuel cell according to claim 1, characterized in that: In the anode support, the mass percentages of the perovskite structural material, the nickel catalytic material and the doped cerium oxide-based material are (1-40):(20-60):(20-60); The nickel catalytic material is nickel oxide; The doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.
5.
3. The solid oxide fuel cell according to claim 1, characterized in that: In the composite electrolyte layer: The thickness of the doped cerium oxide electrolyte layer is 1 to 50 microns; The thickness of the copper-modified doped zirconium oxide electrolyte layer is 0.01 to 5 microns; The thickness of the copper-modified doped cerium oxide electrolyte layer is 1 to 10 microns.
4. The solid oxide fuel cell according to claim 1, characterized in that: The composite cathode layer is a cobalt composite cathode layer, comprising lanthanum strontium cobalt iron powder and doped cerium oxide-based material; The thickness of the composite cathode layer is 10-100 microns; The doped cerium oxide-based material is Ln m Ce 1-m O2, Ln is one or more of La, Gd, Sm, 0.1≤m≤0.5; The weight ratio of the lanthanum strontium cobalt iron powder to the doped cerium oxide-based material is (30-100): (40-70).
5. The solid oxide fuel cell according to claim 1, characterized in that: In step (1), the composite process of the anode support includes a tape casting method and an extrusion molding method; In step (3), a composite cathode layer is prepared on the copper-modified doped cerium oxide electrolyte layer by a coating method, and the high temperature calcination treatment is 800-1200 o C.
6. The solid oxide fuel cell according to claim 5, characterized in that: In step (3), the coating method includes screen printing or film coating.
7. Use of the solid oxide fuel cell according to any one of claims 1 to 6 in energy conversion.
Citation Information
Patent Citations
Metal supported solid oxide fuel cell
CN105531861A
High-activity sulfur-poisoning-resistant solid oxide fuel cell anode catalyst
CN113224328A
Low-temperature high-performance solid oxide fuel cell and preparation method thereof
CN115020741A
High-activity anti-carbon deposition solid oxide fuel cell anode catalyst
CN115133042A